Purification and characterisation of Bile-salt activated lipase (BSAL) enzyme from bovine (Bos taurus) pancreas - Reshidan, Nur Hidayah; Affendy, Norliza Bahtiar; Jonet, Mohd Anuar; Lamasudin, Dhilia Uddie; Ariffin, Zaidah Zainal; Mat Zain, Mazatulikhma; Abd Hamid, Umi Marshida (University of Malaya, 2025)
Bile salt-activated lipase (BSAL) is one of the pancreatic lipases that plays a critical role in the digestion and absorption of dietary fats. Objective: This study aimed to purify bile salt-activated lipase (BSAL) from bovine (Bos taurus) pancreatic tissue. Methods: Bovine pancreas was freshly collected from Abattoir Complex, Department of Veterinary Services, Shah Alam, Malaysia. The fats were removed by trimming grossly visible fat, and extraction was performed using organic solvents. The BSAL was purified by anion exchange chromatography and sent for protein identification by liquid chromatography-mass spectrometry (LC-MS/MS). Successful purification of bovine BSAL was visualised as a single protein band on sodium dodecyl sulphate-polyacrylamide (SDS) gel, which LC-MS/MS confirmed as a bovine BSAL (Accession number – P30122) with a molecular mass of 65.12 kDa and calc pI of 5.57. Peptide identification based on the MS spectrum found 200 predictive peptides, ten sequences with bovine BSAL peptide characteristics. The selected predictive peptide sequences have a molecular mass of 1104.60-3378.94 Da with Qvality q-value greater than 0.01 and XCorr Sequest HT value ranging from 2.6 to 6.8. The specific lipolytic enzyme activity of bovine BSAL was comparable with the positive control, as measured using lipase assay. In conclusion, the results of this study indicate the effectiveness of bovine BSAL purification by anion exchange chromatography from fresh pancreatic tissue and may have the potential for further Halal pharmaceuticals and medical applications.